Maritime law - Baatz, Yvonne (Sweet & Maxwell, 2011)
Southampton on Shipping Law, from the Institute of Maritime Law at Southampton, introduces the reader to maritime law in a concise and accessible style. Suitable for University students the title covers the key areas required for Maritime courses. Authored by a team of experts in the field, this book will become a trusted source in your studies.